1984
DOI: 10.1073/pnas.81.15.4800
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cis and trans X-Pro peptide bonds in proteins by 13C NMR: application to collagen.

Abstract: Heretofore the complexity of natural abundance spectra has precluded the use of 13C NMR to detect cis peptide bonds in proteins. We have incorporated [4-'3C~pro-line into chicken calvaria collagen and report here well-resolved Cy signals, arising from cis and trans X-Pro and X-Hyp peptide bonds (where X is any amino acid residue) in the 13C NMR spectrum of the thermally unfolded protein. Measurement of 13C signal areas shows that 16% of the X-Pro and 8% of X-Hyp bonds are cis in the unfolded collagen. These re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
36
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 23 publications
9
36
0
Order By: Relevance
“…Hence, we concluded that Pro 672 is in the trans conformation and not in a cis-trans equilibrium state 17,18…”
Section: Resultsmentioning
confidence: 83%
“…Hence, we concluded that Pro 672 is in the trans conformation and not in a cis-trans equilibrium state 17,18…”
Section: Resultsmentioning
confidence: 83%
“…Cis peptide bonds involving proline arise in proteins (e.g., see ref. 27) and in synthetic linear and cyclic peptides (28).…”
mentioning
confidence: 99%
“…Seminal work on the structure and dynamics of the extracellular collagen matrix in bone and other tissues was published as far back as 1980 by Denis Torchia and his group [31][32][33][34][35][36][37] and earlier than that on the characterization of proline structure and conformation in peptides [38,39] (albeit in solution), work that has significant relevance for understanding the structural properties of collagen in bone as will become apparent through this discussion. That many of these papers are not highly cited in the biological literature is most likely a consequence of his work being far ahead of its time.…”
Section: Probing the Organic Matrix Structurementioning
confidence: 99%